Life as miracle: some keys of Víctor Erice’s filmography - Latorre, Jorge (2022)
Despite his scarce productions, Victor Erice (1940) is one of Spain’s most renowned teacher of film makers. Cult author, slow and obsessed in his themes, jealous on its soberanity as an artist, he made a cinema counterclockwise the rules of the market, although his three productions received important European awards. It is a cinema that talks of universal human issues from the author’s perspective. A film production more proper for a museum than for the mass entertainment circuit.